Undersociality is unwise. Issue 1 (21st December 2022) - Kumar, Amit; Epley, Nicholas
Abstract: Wise decisions are often guided by an accurate understanding of the expected values of different possible choices. In social contexts, wisdom comes from understanding how others are likely to respond to one's actions, enabling people to make choices that maximize both their own and others' outcomes. Our research suggests that miscalibrated social cognition may create a systematic barrier to wiser decisions in social life. From expressing appreciation to offering support to performing acts of kindness, this program of research indicates that decisions to engage with others are driven by how people expect a recipient to respond, but that people consistently underestimate how positively others will respond to their other‐oriented actions. Because connecting with others consistently increases people's own wellbeing, miscalibrated social cognition may lead to undersociality : being overly reluctant to reach out and connect with others. Miscalibrated expectations about social engagement can create markets for products that help people overcome these barriers in order to consume their time, money, and effort more wisely.